2020
DOI: 10.21100/msor.v18i3.1079
|View full text |Cite
|
Sign up to set email alerts
|

Supporting nursing students’ mathematical understanding

Abstract: A key component of any nursing course is the ability to confidently, and competently, use basic mathematical skills. Indeed, without such skills they would be unable to work safely and successfully in the profession (McMullan, Jones, and Lea, 2012; Choudhary and Malthus, 2017). Furthermore, many nursing students come on to their courses having not studied any form of formal mathematics for years and are very likely to have some form of maths anxiety (McMullan, Jones, and Lea, 2012). sigma Maths Support at Cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It may have been expected that students' ability in the different sections of the test would have differed by grade, as has been shown in previous studies (e.g. Lawson, 2003;Hodds et al, 2020), however the results for 2020 students are consistent across all grades. This therefore suggests that students in 2020 coming to Coventry University had similar strengths and weaknesses regardless of the A level grade achieved.…”
Section: Grade and Sectionmentioning
confidence: 60%
See 1 more Smart Citation
“…It may have been expected that students' ability in the different sections of the test would have differed by grade, as has been shown in previous studies (e.g. Lawson, 2003;Hodds et al, 2020), however the results for 2020 students are consistent across all grades. This therefore suggests that students in 2020 coming to Coventry University had similar strengths and weaknesses regardless of the A level grade achieved.…”
Section: Grade and Sectionmentioning
confidence: 60%
“…Indeed, recent studies have shown the effectiveness of diagnostic testing, particularly for non-mathematicians, when they are accompanied with other measures that support both staff and students (e.g. Hodds, 2020). This paper reports data from a single UK university that compares the entry competencies of a sample of those students who entered with A level mathematics in September 2020 against students with A level mathematics in the two years prior (2019 and 2018 entry).…”
Section: Introductionmentioning
confidence: 99%
“…The test is usually tailored to suit the level of mathematics required by the course. Diagnostic tests have been shown to be effective at providing both staff and students with vital information regarding areas of strength and weakness (e.g., Hodds, Shao, and Lawson, 2020) as well as increasing pass rates in Engineering (Patel and Little, 2006) and Nursing (Hodds, 2020) when combined with tailored support packages. Due to the disruption to education caused by the pandemic, diagnostic tests are perhaps more vital than ever in helping staff to determine the true competency of students whilst also providing support in the best possible way on arrival at university.…”
Section: Introductionmentioning
confidence: 99%